"This is my portfolio" : portfolios in upper secondary school English studies - Pollari, Pirjo (2000)
This qualitative case study describes a portfolio programme in the teaching of English as a foreign language in two Finnish upper secondary schools. Approximately 100 students participated in the portfolio programme, whose topic area was culture. Firstly, the purpose of this action research was to try out and develop portfolios in foreign language teaching as a pedagogical innovation. Secondly, the aim was to foster students' empowerment, i.e. their active and responsible role in learning. Thus, the primary research interests were twofold: How did the portfolio programme proceed and progress? Did the portfolio programme foster the students' empowerment? The present report is divided into three parts. Part I presents the theoretical framework, Part II describes and evaluates the process of the portfolio programme and Part III introduces and analyses different portfolio profiles and portraits emerging from the data. The results were promising. A great majority of the students both liked the portfolio approach and took charge of their learning. Thus, the portfolio seemed to offer a vehicle for students' empowerment. However, there were also some students who disliked the portfolio course. They found the topic area uninspiring and the student-centred and self-directed approach inefficient, difficult or unsuitable for themselves.